Documentary Film Design of Burlap Cloth Craft as Local Product Development of Bandung Creative Industries - Feby Gusman; Puri Kurniasih; Yulianto Hadiprawiro (Visual Heritage: Jurnal Kreasi Seni dan Budaya, 2022)
This paper is a summary of the result of final task research “Documentary Film Design of Burlap Cloth Craft as Local Product Development of Bandung Creative Industries” in 2020. The purpose of this research was to design a documentary film of burlap cloth craft as creative industry of burlap cloth processing. This documentary is expected to be able to evoke the craft of burlap cloth to have more selling value. This research uses a qualitative method by searching and collecting literature, observations and interviews about burlap cloth craft. Based on the result, the conclusion is that people prefer branded and high-priced better than choosing local products that are cheap, environmentally-friendly and, durable. Documentation is needed with an easy-to-understand visual style to introduce burlap cloth craft to the public. Thus, this research produced a documentary film that uses supporting effects to attract the interest of the audience and themed the processing of burlap craft as a creative industry product that can be understood by the audience.